The concept of homestay on food sources and food preparation / Nur Asma Diyana Azman and Nurashikin Karim - Azman, Nur Asma Diyana; Karim, Nurashikin (2017)
Homestay program is one of the most popular services in the hospitality industry nowadays and the development of the service is rapidly being expanded as compared in the past. So, the main purpose of this undergraduate project report is to identify and elaborate the actual concept of homestay program in Malaysia specifically from the aspect of food sources and food preparation. Moreover, this research project also discussed on the misconception of a homestay that happening todays. In order to get a reliable data, the study used a cross-sectional descriptive research design whereby a quantitative technique is the most appropriate way. The researchers had distributed questionnaire to the homestay operators of two districts in Kedah, which are Sik and Baling to get all the information needed in this study before analyzed by using SPSS software.